2004
DOI: 10.1111/j.1365-2559.2004.01804.x
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal follicular lymphoma: a clinicopathological and genetic analysis of 15 cases arising at non‐cutaneous extranodal sites

Abstract: The low incidence of t(14;18) and favourable outcome encountered in ENFL in this study is similar to that previously found for primary cutaneous FL. These results support the concept of a subtype of FL lacking t(14;18) involving the major breakpoint cluster region, and with a propensity to arise at extranodal sites. Despite a high relapse rate, patients with ENFL are more likely to achieve complete remission and may ultimately have a more favourable long-term prognosis than those with equivalent nodal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 38 publications
5
51
1
Order By: Relevance
“…The present study found no difference in survival between t(14;18)-positive and -negative groups in conjunction with studies of extranodal follicular lymphomas outside the ocular adnexal region (Goodlad et al 2004;Weinberg et al 2009;Relander et al 2010). However, only patients with the t(14;18) had recurrence.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The present study found no difference in survival between t(14;18)-positive and -negative groups in conjunction with studies of extranodal follicular lymphomas outside the ocular adnexal region (Goodlad et al 2004;Weinberg et al 2009;Relander et al 2010). However, only patients with the t(14;18) had recurrence.…”
Section: Discussionsupporting
confidence: 64%
“…Other early stage extranodal follicular lymphoma studies have reported that approximately 50% of the tumours exhibited the translocation (Goodlad et al 2004;Weinberg et al 2009). For the group of patients with disseminated lymphoma, the rate was 83%, in accordance with other studies (Kuppers 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary involvement of extranodal areas is also very uncommon [14]. The bone marrow is involved in 50% to 60% of the cases.…”
Section: Signs and Symptommentioning
confidence: 99%